Investigating the Role of Digital marketing, price perception, customer satisfaction and its impact on marketing performance - Prayuda, Rafie Zaidan (AGUSPATI Research Institute, 2024)
This research aims to analyze the determinants of customer satisfaction and their impact on marketing performance. The research method used is a quantitative research method. This research data uses primary data through questionnaires to 90 respondents. The research sample was taken using purposive sampling. The analysis method used is Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. The research results show that partially digital marketing and price perception have a positive and significant effect on customer satisfaction. Partially, digital marketing and price perception and customer satisfaction have a positive and significant effect on marketing performance